2011
DOI: 10.1371/journal.pntd.0001334
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Changes and Clinical Responses of Buruli Ulcer Plaque Lesions during Chemotherapy: A Role for Surgical Removal of Necrotic Tissue?

Abstract: BackgroundBuruli ulcer (BU) caused by Mycobacterium ulcerans is a necrotizing skin disease usually starting with a subcutaneous nodule or plaque, which may ulcerate and progress, if untreated, over months and years. During the currently recommended antibiotic treatment with rifampicin/streptomycin plaque lesions tend to ulcerate, often associated with retarded wound healing and prolonged hospital stays.Methodology/Principal FindingsIncluded in this study were twelve laboratory reconfirmed, HIV negative BU pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 18 publications
2
39
0
Order By: Relevance
“…Then, the histopathological findings change into significant infiltrates of inflammatory cells including granuloma formation. 13 Retrospectively, the lesion was relatively localized almost within the visual inspection, and the preoperative mapping biopsy revealed not only massive necrosis but also granuloma formation, which suggested that host immune defense had already worked as described above, contrary to our expectation based on the fact that the lesion was treated improperly with occlusive dressing. We cannot find any obvious evidences which suggest that the lesion of this case became exacerbated due to occlusive dressing.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Then, the histopathological findings change into significant infiltrates of inflammatory cells including granuloma formation. 13 Retrospectively, the lesion was relatively localized almost within the visual inspection, and the preoperative mapping biopsy revealed not only massive necrosis but also granuloma formation, which suggested that host immune defense had already worked as described above, contrary to our expectation based on the fact that the lesion was treated improperly with occlusive dressing. We cannot find any obvious evidences which suggest that the lesion of this case became exacerbated due to occlusive dressing.…”
Section: Discussionmentioning
confidence: 67%
“…Local immunosuppression dissolves when the burden of mycobacterial toxin is reduced due to the success of the antibiotic treatment. Then, the histopathological findings change into significant infiltrates of inflammatory cells including granuloma formation …”
Section: Discussionmentioning
confidence: 99%
“…Additional features, more typical for an untreated BU lesion, include fat cell ghosts and minimal perivascular infiltration. 58,59 Management Although spontaneous healing of BU can be seen in up to one-third of cases, this can take months and lead to deep scarring, contractions, and disfiguring scars (Fig. 2).…”
Section: Managementmentioning
confidence: 99%
“…In 2004, the WHO introduced the use of the combination of streptomycin and rifampicin given daily for 8 weeks as treatment [14]. However, surgery and wound management remain critical aspects of BU care [15], [16].…”
Section: Introductionmentioning
confidence: 99%